REGIONAL ASPECTS OF BANKING SYSTEM DEVELOPMENT IN CASE OF WESTERN BORDER AREAS OF UKRAINE - O. M. Yunko (Фінансово-кредитна діяльність: проблеми теорії та практики)
One of the key factors to ensure the proper development of regions is the functioning of banking institutions in them. It is bank as an independent financial institution, accumulating temporarily free funds of legal entities and the population, by active operations creates serious infusion into the economy of the region in the form of investment, financing some separate areas of the business entities economy. The regional banking system affects the whole region development, thereby creating the conditions for active investment, ensuring adequate financing of companies, and thus increasing production and employment and, consequently, improving people's lives level. With the expansion of the European Union the western border of Ukraine acquired a new meaning. Therefore, was analyzed the state of the banking sector in western border regions of Ukraine and were examined existing regional disparities in the development of the regional banking system. The results of empirical analysis of the process are given. The recommendations on the development of the credit market of Western Ukrainian region are provided.